Strengthening the Healthy Adult Self in Art Therapy: Using Schema Therapy as a Positive Psychological Intervention for People Diagnosed With Personality Disorders - Haeyen, Suzanne (Frontiers in Psychology, 2019)
This article reviews recent theoretical contributions and studies about art therapy that attempt to capture aspects of healthy ego functioning and presents an inventory of art therapy interventions to strengthen the Healthy Adult. It discusses how art therapy can offer interventions that focus specifically and directly on the integration and growth of the whole person, and which interventions are suitable for this purpose in the treatment of people diagnosed with severe personality disorders. A link is made between the Healthy Adult as a familiar concept from Schema Therapy, and Positive Psychology, with its focus on well-being, strength and positive affect. On the basis of our present knowledge, available studies and experiences, art therapy seems promising in contributing to the development of Healthy Adult functioning. Art therapy addresses the different areas of healthy adult functioning. Specific art therapy interventions are discussed on a concrete level. Art therapy appears to offer ways to strengthen the Healthy Adult and helps people to free themselves from destructive patterns and to work on satisfying their basic needs as independent and responsibly functioning individuals in a positive connectedness with themselves and their surroundings. The strength of art therapy may be the experiential level and the appeal to the capacity to play, to flexibility, and to be creative. This makes experiences easier to reach, and developing from there into a Healthy Adult mode is possible in a manner that is more felt than thought. Creativity can be regarded as the ability of the Healthy Adult to be flexible and to find different solutions to a problem. This appeal of art therapy fits well the therapeutic goal of empowerment and well-being, which is at the heart of positive psychology. More research is needed to verify the effects and working mechanisms of art therapy interventions.